Internal Carotid Artery Aneurysm Mimicking Peritonsillar Abscess - Jacek Brzost; Anna M. Cyran; Martyna Waniewska; Miroslaw J. Szczepanski (Case Reports in Otolaryngology)
The extracranial internal carotid artery aneurysm (EICAA) is an uncommon arterial lesion. Patients typically present with neurologic symptoms resulting from impaired cerebral perfusion and compression symptoms of cranial nerves. Often EICAA presents as a pulsatile neck mass, which is otherwise asymptomatic. We present a case of an 84-year-old female, who was initially referred to the Emergency Department for Otolaryngology with suspected peritonsillar abscess. The patient had a history of recent upper airway infection and cardiovascular comorbidities, including hypertension and ischaemic stroke complicated by extensive neurologic deficits. Physical examination revealed a compact, nonpulsatile mass in the lateral parapharyngeal space and local erythema of the mucosa. Duplex Doppler Ultrasonography and Computed Tomography revealed an atherosclerotic aneurysm of the right internal carotid artery, measuring 63×55×88 mm, stretching from the skull base to the angle of the mandible.